Seismic-Proof Buildings in Developing Countries - Laghi, Vittoria; Palermo, Michele; Trombetti, Tomaso; Schildkamp, Martijn (Frontiers in Built Environment, 2017)
The use of “ductile seismic frames”, whose proper seismic behavior largely depend upon construction details and specific design rules, may do not always lead to effective seismic resistant structures, as dramatically denounced by the famous Chinese artist Ai Weiwei in his artwork Straight. The artwork (96 tons of undulating metal bars that were salvaged from schools destroyed by the 2008 Sichuan, China earthquake, where over 5,000 students were killed) is a clear denounce against the corruption yielding to shoddy construction methods. The issue of safe constructions against natural hazards appears even more important in developing countries where, in most cases, building structures are realized by non-expert workers, or even by simple “people from the street”, who does not have any technical knowledge on construction techniques and seismic engineering. In the present paper, a brief history from the first frame structures to the more efficient wall-based structures is provided within earthquake engineering perspectives. The superior structural properties of box-type wall structures with respect to conventional frame structures envisage a change of paradigm from actual “ductility-based” Earthquake Engineering (centered on frame structures) towards 100% safe buildings through a “strength-based” design exploiting the use of box-type wall based structures.